Study protocol—Evoked craving in high-dose benzodiazepine users - Zamboni, Lorenzo; Toldo, Silvia; Fusina, Francesca; Mattiello, Matteo; Mannari, Vanessa; Campagnari, Simone; Schiavone, Valentina; Congiu, Alessio; Verlato, Giuseppe; Chiamulera, Cristiano; Lugoboni, Fabio (Frontiers in Psychiatry, 2022)
BZD abuse, especially concerning high doses of BZDs, is an impairing substance use disorder (SUD) which is often difficult to treat. Craving and cue reactivity (CR) are two important phenomena that contribute to maintaining addiction and to triggering relapses in BZD abuse, but that have nevertheless rarely been addressed in scientific literature. The present study aims to fill these gaps by implementing a highly innovative virtual reality (VR) design to assess the impact of substance-related environmental cues on BZD craving, as well as their influence on patients’ affective state. Therefore, on one hand, the research will contribute to the assessment of VR feasibility in the study of these phenomena, and on the other, it will help to disentangle the role that CR and craving have on equally important factors to consider when treating SUD, such as mood and attention. We will recruit a healthy control group, and a patient group comprising people seeking treatment for BZD detoxification. The experimental design will consist in the presentation of three VR scenarios, one neutral, one BZD-related but without BZD cues, and another with BZD cues. Craving will be measured through a virtual analog scale (VAS), and the POMS and AAS questionnaires will also be administered. We will additionally control for VR-induced feelings of sickness by administering the SSQ, and the PQ to investigate participants’ sense of presence in the virtual environments. We expect patients to exhibit higher levels of craving, and that craving will be higher after exposure to a cue-related virtual environment as compared to a neutral scenario.